Civil Society, Regulatory Space and Cultural Authority in China’s Television Industry - Keane, Michael (Television, Regulation and Civil Society in Asia, 2002)
The question of why civil society presents such appeal for commentators, scholars and journalists writing about developing nations is an important one. The most likely explanation is that a kind of global faith exists in civil society as the driving force of a new world order. This global transformation, exemplified by the collapse of the Soviet bloc, celebrates people’s freedom to participate in public discourse, and ultimately in processes of directly electing political representatives. In this sense the concepts of civil society and the public sphere come together to describe a global anti-authoritarian groundswell where the power of ideas is linked to global cultural development.
Num Pages: 5
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); Australie (lieu de production du savoir); Chine (corpus analysé); _Nettoyé